The Hulong hybrid grouper (Epinephelus fuscoguttatus♀×Epinephelus lanceolatus♂) has invaded the coastal waters of Hainan Island, China - Zhang, Xiang; Li, Jianlong; Chen, Sizhu; Yang, Qingyan; Ji, Fei; Luo, Huigui; Ding, Shaoxiong (Frontiers in Marine Science, 2024)
Nowadays, various types of hybrid groupers have been successfully applied in the mariculture industry in the southwest Pacific coastal area, raising public concern about potential biological invasions. As the earliest produced hybrid grouper with the highest yield worldwide, the Hulong hybrid grouper (Epinephelus fuscoguttatus♀× Epinephelus lanceolatus♂, also known as the Sabah grouper) was first produced in Malaysia in 2007 and subsequently developed in mainland China in 2009. With the development of the breeding and mariculture industry of the Hulong hybrid grouper on Hainan Island, escapees have been sighted in the coastal waters of Hainan Island for years. Their current distribution includes all the coastal waters of Hainan Island, with a preference for inshore reef and artificial structure areas. Based on social investigations and specimen collections, this species has been continuously present for at least 12 years in multiple locations. The growth and gonadal development status of this hybrid grouper indicate the long-term survival and population establishment of the Hulong hybrid grouper in the wild. The mechanisms of their introduction include unintentional escapees from the aquaculture industry as well as intentional releases. This study documents the first artificial hybrid marine fish to invade and establish a population in the wild. The negative ecological impacts of the Hulong hybrid grouper on the biodiversity and ecosystem such as interspecies competition, disease transmission and genetic pollution were further discussed.